CORPORATE DYNAMICS: Exploring the Nexus of Company Size, Leverage, Profitability, and the Regulatory Role of Variable Tax Aggressiveness - Marendra, I Gede (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
Tax avoidance is one of the efforts to minimize the tax burden that is often carried out by companies, because it is still within the framework of applicable tax regulations. The purpose of this study is to empirically prove the effect of Company Size, Leverage, Profitability simultaneously on Company Value in mining sector companies listed on the IDX in 2017-2021, the total population in this study is 47 companies. Samples were obtained using the purposive sampling method, so 41 companies were obtained. The research approach used in this study is quantitative research. The secondary data used is obtained from financial statements according to the selected criteria. The data collection method is carried out using purposive sampling by processing data using the Eviews software tool version 9. Data analysis using Panel Data Regression and Moderating Regression Analysis. Based on the paired test model using Chow Test, Hausmant Test and Lagrange Multiplier Test, the best model used is the Fixed Effect Model. The calculation results state that Company Size, Leverage and Profitability together have a significant positive effect on the Company Value of Mining Companies listed on the Indonesia Stock Exchange during the 2017-2021 period.